Local mechanical stress relaxation of Gunn diodes irradiated by protons; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Gradoboev A. V. Aleksandr Vasilyevich (Radiation physics and chemistry of condensed matter, 2017)
Title screen